PENGARUH CORPORATE IMAGE, KUALITAS JASA PENDIDIKAN, HARGA DAN WORD OF MOUTH TERHADAP KEPUTUSAN MAHASISWA MEMILIH MELANJUTKAN STUDI DI MAGISTER MANAJEMEN FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TANJUNGPURA - admin, Norita Ardelina B11112028 (Jurnal Manajemen Update, 2017)
This study aimed to analyze whether the variable Corporate Image, Educational Service Quality, Price, and Word of Mouth toward students decision who continue the study in Management Magister Economy and Business Faculty, Tanjungpura University. Data analysis technique used multiple regression linier using program SPSS version 17.0. Data used is primer data collected from 80 students of Management Magister program in Economy and Business Faculty, Tanjungpura University. The results of study show that (1) Corporate Image had significant influence toward educational service decision, (2) Educational Service Quality had significantÂ  influence toward educational service decision, (3) Price had not significantÂ  influence toward educational service decision, and (4) Word of Mouth had significant influence toward educational service decision. Keyword: Corporate Image, Educational Service Quality, Price, Word of Mouth, Purcashe Decision